The opportunistic pathogen Encephalitozoon cuniculi in wild living Murinae and Arvicolinae in Central Europe - Perec-Matysiak, Agnieszka; Leśniańska, Kinga; Buńkowska-Gawlik, Katarzyna; Čondlová, Šárka; Sak, Bohumil; Kváč, Martin; Rajský, Dušan; Hildebrand, Joanna (European journal of protistology, 2019)
Encephalitozoon spp. is an obligate intracellular microsporidian parasite that infects a wide range of mammalian hosts, including humans. This study was conducted to determine the prevalence of Encephalitozoon spp. in wild living rodents from Poland, the Czech Republic and Slovakia. Faecal and spleen samples were collected from individuals of Apodemus agrarius, Apodemus flavicollis, Apodemus sylvaticus, and Myodes glareolus (n = 465) and used for DNA extraction. PCR, targeting the ITS region of the rRNA gene was performed. The overall prevalence of microsporidia was 15.1%. The occurrence of Encephalitozoon cuniculi in the abovementioned host species of rodents has been presented for the first time, with the highest infection rate recorded for A. flavicollis. Sequence analysis showed that the most frequent species was E. cuniculi genotype II (92.5%). E. cuniculi genotypes I (1.5%) and III (6.0%) were also identified.
Keywords: Small rodents; encephalitozoonóza; polymerázová řetězová reakce; fylogeneze; Phylogeny; Animals, Wild; Europe; prevalence; Murinae; divoká zvířata; nemoci hlodavců; mezerníky ribozomální DNA; Evropa; Animals; Encephalitozoon cuniculi; zvířata; Prevalence; Arvicolinae; Rodent Diseases; DNA, Ribosomal Spacer; Molecular analysis; Polymerase Chain Reaction; Microsporidia; Encephalitozoonosis